Determining the costs of delay in the Philippine criminal justice system - Ang, Alvin (2006)
Criminal justice systems are mostly concerned with dispensing justice accurately rather than the efficiency of the processes involved within the system. With such prioritization, delays become part of the process, which in turn can negatively affect the accused, accuser and society as a whole. While there is an implicit general awareness that delays have costs, there have been few attempts to actually estimate them. However, without such an estimaate, there will be a vague understanding of how big or small its impact is on society.

In this paper, I offer a framework for estimating such costs. Specifically, I consider the case of the Philippines. With this framework, I have estimated the cost of delay to the Philippine Criminal Justice System as approximately half of the budget allocated to it for the year 1998. This gives us now a clear idea of why efficiency should be an equally important goal of the system as accurately dispensing justice.
Keywords: Criminal justice system